2022
DOI: 10.1111/jce.15379
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ablation index versus time‐guided radiofrequency energy dosing using normal and half‐normal saline irrigation in a porcine left ventricular model

Abstract: Background Ablation Index (AI) is a multiparametric quality marker to assess the durability of radiofrequency (RF) lesions. The comparative effectiveness and safety of AI versus time‐based energy dosing for ablation of ventricular arrhythmias are unknown. Objective We compared AI and time‐based RF dosing strategies in the left ventricles (LVs) of freshly harvested porcine hearts. Methods Ablation was performed in vitro with an open‐irrigated ablation catheter (Thermocool ST/SF), 40 W, contact force 10–15 g. Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 13 publications
1
16
1
Order By: Relevance
“…In this context, Gasperetti ventricular outflow tract when using the AI to guide ablation (target values 590 in the free wall and 610 in the septum). 19 Of interest, Gasperetti et al reported no SP despite target AI values substantially higher than those shown to increase the risk of SP in the present study by Larsen et al 18 The reasons for this apparent discrepancy warrant further investigation, although they may be related to the…”
Section: Funding Informationcontrasting
confidence: 53%
See 2 more Smart Citations
“…In this context, Gasperetti ventricular outflow tract when using the AI to guide ablation (target values 590 in the free wall and 610 in the septum). 19 Of interest, Gasperetti et al reported no SP despite target AI values substantially higher than those shown to increase the risk of SP in the present study by Larsen et al 18 The reasons for this apparent discrepancy warrant further investigation, although they may be related to the…”
Section: Funding Informationcontrasting
confidence: 53%
“…In this context, Gasperetti et al have recently shown improved long‐term outcomes of catheter ablation of premature ventricular complexes from the right ventricular outflow tract when using the AI to guide ablation (target values 590 in the free wall and 610 in the septum) 19 . Of interest, Gasperetti et al reported no SP despite target AI values substantially higher than those shown to increase the risk of SP in the present study by Larsen et al 18 The reasons for this apparent discrepancy warrant further investigation, although they may be related to the specific experimental conditions tested by Larsen et al (i.e., stable contact force and catheter orientation, fixed power) which may not be reproducible or obtainable in the clinical setting. Additional limitations that have been highlighted also by the authors include the lack of generalizability to RF lesions within abnormal substrates and the potential analytical bias due to collinearity between AI and lesion duration, particularly considering that the other variables included in the AI calculation such as contact force and power were maintained constant per study protocol.…”
mentioning
confidence: 45%
See 1 more Smart Citation
“…Available clinical and experimental data also support that the type of irrigation, be it a discrete number of pores or a surround flow designs, has no significant impact on lesion size. (2,3,10,18,19,20) Our study also suggests that the incidence of steam pops is not directly related to the amount of irrigation. Whether the type of irrigation, discrete vs surround flow, has an impact on pop occurrence remains unclear.…”
Section: Impact Of Blood Flow and Catheter Irrigationmentioning
confidence: 53%
“…Available clinical and experimental data also support that the type of irrigation (ie, discrete number of pores or surround flow designs) has no significant impact on lesion size. 2 , 3 , 10 , 18 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%